High-purity hydrogen production from phenol on Ni-CaO-Ca12Al14O33 multifunctional catalyst derived from recovered layered double hydroxide. (15th January 2023) - Dang, Chengxiong; Liang, Shuling; Yang, Wenwen; Cai, Weiquan
Graphical abstract: A recovery approach of Ni-Ca-Al layered double hydroxide (LDH) structure is developed to produce wormhole-like Ni-CaO-Ca12 Al14 O33 bifunctional catalyst, which exhibits excellent stability in sorption-enhanced steam reforming of phenol for producing high-purity H2 . Highlights: The multifunctional catalyst is prepared from rehydrated layered double hydroxide. Adsorbed tetracycline forms carbon template to achieve a wormhole-like structure. 98.3 vol% H2 is stably produced from phenol with CO2 capture in 50 cyclic tests. Abstract: Hydrogen production with in situ CO2 capture by the sorption-enhanced steam reforming (SESR) technology is a promising concept to reduce anthropogenic CO2 emissions. A serious disadvantage of SESR processes is the rapid, sintering-induced decay of its cyclic performance. Here, a recovery approach of Ni-Ca-Al layered double hydroxide (LDH) structure with adsorbed tetracycline to develop a multifunctional catalyst is exploited. The in situ formation of carbon template originating from the adsorbed tetracycline allows for the emergence of favorable structure possessing excess porosity along with deposition of small nanoparticles, thus providing physical isolation to inhibit the sintering of Ca and Ni species. As such, 98.3 vol% H2 was stably produced from phenol in 50 cyclic tests, during which only 33 % decrease of sorption-enhancement effect was observed, ensuring superior SESR of phenol performance. This strategy provides a new paradigm for the rational design of materials derived from LDH for high-temperature reactions.